(untitled) (Kathmandu University Medical Journal, 2022)
Background Systemic hypertension is one of the most common chronic, debilitating diseases prevalent in the modern era, with many complications in terms of stroke, chronic kidney disease, coronary artery disease and retinopathy. When it comes to the eye, as a target organ damage, it leads to one of the many vision threatening conditions, hence degrading the quality of life. Early detection and subsequent management of patients at risk of hypertensive retinopathy serves to be a crucial panacea in the treatment course. Objective To investigate the characteristics retinal findings among hypertensive population and analyze the associated risk factors. Method A hospital based prospective study was conducted, among 250 patients presenting to ophthalmology outpatient department in Dhulikhel Hospital, Kathmandu University Hospital (DH-KUH), over a time span of 6 months, to analyze hypertensive retinopathy and its implications. Fundus examination under mydriasis was done on all subjects and hypertensive retinopathy was graded according to the modified Scheie classification. Result Most patients belonged to age group of 56-65 years (30%). Nearly half (48%, N=120) of the hypertensive population had some forms of retinopathy. Grade II hypertensive retinopathy (24.8%) was the most common hypertensive change observed. Majority (55%) of the patients with retinopathy were smokers. About two-third of the subjects (67.5%) had been diagnosed to have hypertension and under treatment for over 5 years. Conclusion The occurrence of retinopathy among hypertensive patients attending ophthalmology department is higher. Awareness regarding systemic hypertension and its effect on ocular health is very important to be disseminated among public. Timely referral among medical specialities could diagnose and prevent curable blindness among hypertensive patients.